The reasons for scientific competencies migration, and its effects on social and economic development (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aimed to know the most important reasons for the scientific competencies migration to developed countries, the attractive factors offered by those countries to immigrants, and its impact on social and economic development, scientific and technical expertise are the cornerstone for the advancement, prosperity, and social development, the expertise losing lead to a drain on the Human capital. The study concluded that migrations benefits in raising the people living level with their families and in increasing financial transfers to the mother country, they carry many negatives for the exporting countries of those brains, as they increase ignorance, backwardness, and dependency, while the receiving countries increase in development and urbanization. at the social, economic, and technological levels.